One Role, Different Expectations: Exploring Teacher Perspectives on Principal Leadership in Indonesian Schools - Lili Puspita Rahayu; Sowiyah Sowiyah; Handoko Handoko; Bujang Rahman (Universitas Negeri Malang, 2025)
This study explores how teachers across different educational levels in Indonesia perceive the ideal characteristics of a school principal. Using an exploratory descriptive design, data were gathered from 1,594 teachers in Lampung Province through an online semi-structured survey. The open-ended responses were thematically analyzed to identify the dominant traits teachers associate with effective leadership. Six recurring themes emerged: assertiveness, wisdom, nurturing, discipline, responsibility, and open-mindedness. However, the emphasis on each trait varied by school level. Elementary teachers prioritized emotional and nurturing leadership; junior high teachers emphasized firmness and structure; while senior high teachers favored democratic and wise leadership. Findings suggest that leadership expectations are shaped by contextual factors such as school level, teacher maturity, and institutional culture. These results align with Vygotsky’s sociocultural theory and Hallinger’s instructional leadership model, highlighting the importance of adaptive, relationship-based leadership. The study calls for leadership development programs that are differentiated and context-sensitive. By integrating teacher perspectives, educational leaders can better align their practices with school-specific needs, enhancing both teacher engagement and school climate.